Placental Growth Factor Level is Lower in Early-Onset Preeclampsia, while Tumor Necrosis Factor Alpha Level does not Show any Difference between Early and Late Onset Preeclampsia - Christofani Ekapatria (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To analyze the difference of PlGF and TNF-α serum level between early-onset and late-onset preeclampsia. Method: This is a cross-sectional analytic comparative study comparing serum level of PlGF and TNF-α between groups with earlyand late-onset preeclampsia. Each group consists of 32 subjects who met inclusion criteria and presented to Dr. Hasan Sadikin Hospital or its district hospitals in September - November 2012. Statistical analysis was performed with Kolmogorov Smirnov test, Saphiro-Wilk test, and non-parametric Mann-Whitney test. Result: Mean of PlGF serum level in the group with early-onset preeclampsia is 53.0344±38.07140 pg/ml, while mean of which in the group with late-onset preeclampsia is 241.8063±192.8373 pg/ml (p<0.0001). Mean of TNF-α serum level in the group with early-onset preeclampsia is 2.7733±0.97533pg/ml, while mean of which in the group with late-onset preeclampsia is 2.5061±0.84872 pg/ml (p= 0.235). Conclusion: Serum level of PlGF in early-onset preeclampsia is lower than the level of which in late-onset preeclampsia (p<0.0001). There is no significant difference of TNF-α serum level between the early- and late-onset preeclampsia (p=0.235). [Indones J Obstet Gynecol 2012; 36-4: 181-4] Keywords: early onset, late onset preeclampsia, PlGF, preeclampsia, TNF-α